2006
DOI: 10.2174/1573406410602060577
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and In Vitro Evaluation of the Anti-Viral Activity of N-[4-(1H(2H)-benzotriazol-1(2)-yl)phenyl]alkylcarboxamides

Abstract: A series N-[4-(1H(2H)-benzotriazol-1(2)-yl)phenyl]alkylcarboxamides (8e-k, 9e-i, k, l) and their parent amines (5a-c and 6a-d) were prepared according to Schemes (1 and 2). Compounds were evaluated in vitro for cytotoxicity and antiviral activity against a wide spectrum of RNA (positive- and negative-sense) viruses, like [Bovine Viral Diarrhea Virus (BVDV), Yellow Fever Virus (YFV), Coxsackie Virus B (CVB-2), Polio Virus (Sb-1), Human Immunodeficiency Virus (HIV-1), Respiratory Syncytial Virus (RSV)] or double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…Compounds (1-6) were evaluated in cell-based assays against the above listed ssRNA þ , dsRNA and ssRNA À viruses, as previously described [1][2][3][4]. Cytotoxicity of compounds was evaluated in parallel with the antiviral activity.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds (1-6) were evaluated in cell-based assays against the above listed ssRNA þ , dsRNA and ssRNA À viruses, as previously described [1][2][3][4]. Cytotoxicity of compounds was evaluated in parallel with the antiviral activity.…”
Section: Resultsmentioning
confidence: 99%
“…Several compounds have been identified as RNA helicase of inhibitors of flavi- and other RNA viruses (Borowski et al, 2007; Carta et al, 2006; Frick, 2007; Johansson et al, 2003; Maga et al, 2005; Wu et al, 2006; Xi, 2007). Borowski et al, (2002) reported a WNV helicase inhibitor which also was active in cellular assays (IC 50 = 25–30 μM).…”
Section: Targeting Critical Functions Of Individual Flaviviral Prmentioning
confidence: 99%
“…10 respectively) and investigated whether they were able to potentiate the antiproliferative activity of doxorubicin (Doxo), vincristine (VCR) and etoposide (VP16) in human tumor derived cell lines carrying the Pgp (Doxo and VCR), or MRP (VP16) phenotype [32].…”
Section: Anticancer Activitymentioning
confidence: 99%